Role of VA-Mycorrhiza in the management of wilt disease of guava in the alfisols of Chotanagpur - S. KUMAR; SUKHADA MOHANDAS1, A.K. SRIVASTAVA, R. AHMED, (Indian Phytopathology, 2002)
A replicated field trial with twelve year old trees of guava cv. Sardar at three levels of Glomus mosseae Gerd. and Trappe l.e, 2.5, 5.0 and 10 kg symbiont mixed with farmyard manure (FYM), that of with and without FYM revealed that VAM reacts with the host pathogen system in a subtle manner. The percent wilting of trees recorded was lower (44.8 to 75.2%, mean 62.0%) in VA-Mycorrhiza treated trees than the two controls (80.6 and 100%, mean 90.3%). However the response was not in accordance with the dosage. Root bit infection and colonisation of VAM revealed 75 to 85% in treated and 50 to 20% in two control series respectively. Fusarium propagule in the rhizosphere of treated plants varied between 2xl01 to 6xlOZ c.f.u. and 8xlOZ to 10xlOZ c.f.uJg soil, respectively. Based on overall performance, use of VAM symbiont at the rate of 5 kg/tree appeared beneficial